Image preprocessing method based on local approximation gradient with application to face recognition. Issue 1 (February 2017) - Li, Zhaokui; Wang, Yan; Fan, Chunlong; He, Jinrong
Abstract In order to obtain more robust face recognition results, the paper proposes an image preprocessing method based on local approximation gradient (LAG). The traditional gradient is only calculated along 0° and 90°; however, there exist many other directional gradients in an image block. To consider more directional gradients, we introduce a novel LAG operator. The LAG operator is actually calculated by integrating more directional gradients. Because of considering more directional gradients, LAG captures more edge information for each pixel of an image and finally generates an LAG image, which achieves a more robust image dissimilarity between images. An LAG image is normalized into an augmented feature vector using the "z -score" method. The dimensionality of the augmented feature vector is reduced by linear discriminant analysis to yield a low-dimensional feature vector. Experimental results show that the proposed method achieves more robust results in comparison with state-of-the-art methods in AR, Extended Yale B and CMU PIE face database.